Measuring the Concentration of Radon Gas in Book Stores in Primary Schools in Diyala Governorate - Jassem Kadhim, Mothana; Ahmed Ebrahiem, Sameera (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In this research, the concentration of radon gas was calculated in the book store rooms of schools in Diyala Governorate, it was calculated by Solid State Nuclear Track Detectors (SSNTDS) when the detector (CR-39) was used, the detector was placed and suspended at a distance of 160 cm from the surface of the earth, and the detector was exposed for 30 days to record alpha tracks. The results of radon concentration showed that the highest concentration percentage was found in (Eishtar) school, which was equal to (84.896) Bq/m3, while the lowest value was recorded in (Habhib) school, which was equal to (11.242) Bq/m3, where the concentration rate was equal to (28.158) Bq/m3. When we compared our results with the global results, we found that the calculated radon concentrations are much less than the internationally permissible limits recorded by (ICRP), which were in the range of (200-300) Bq/m3.